TOURIST DESTINATION DEVELOPMENT STRATEGIES AND THE IMPACT ON TOURIST VISITS CASE STUDY: PURA GUNUNG KAWI IN SEBATU VILLAGE, GIANYAR, BALI - I Made Sudjana; I Made Darsana (Journal of Business on Hospitality and Tourism, 2018)
Pura Gunung Kawi Sebatu is a tourist destination in Bali. The temple is located in Sebatu Village, Tegallalang, Gianyar Regency. However, unlike most tourist destinations in general, Gunung Kawi Temple is infrequently visited by both foreign and domestic tourists, especially when compared with similar destinations, such as Pura Tirta Empul Tampaksiring. The purpose of this study is to determine the development strategy of “Pura Gunung Kawi Sebatu” and the impact of tourist visits on the welfare of community in Sebatu Village. This study used qualitative descriptive approach which aims to describe, record, analyze, and interpret current conditions of Pura Gunung Kawi Sebatu. The results from this study is the development strategies of Pura Gunung Kawi relies on some factors such as: the stability of various levels, such as security, comfort, support facilities and infrastructure; the quality and quantity of human resources; partnerships with funding agencies; the linkage function development of tourism activities; increased community participation in tourism development; and programs implementation for effective promotion on an ongoing basis. These stabilities help increase the number of tourist visits, which leads to community’s welfare in the area surrounding Pura Gunung Kawi Sebatu.